Nanostructural manipulations for achieving record-high room temperature figure of merit in the ZnSb thin films. (December 2021) - Zheng, Zhuang-Hao; Wang, Tao; Yang, Dong; Jabar, Bushra; Abbas, Adeel; Li, Fu; Chen, Yue-Xing; Zha, Xian-Hu; Liang, Guang-Xing; Fan, Ping
Abstract: Recently, fabrication of high-efficiency miniature thermoelectric devices with thin films has attracted great attention. ZnSb-based thin films have been widely studied owing to their advantages of earth-abundant, eco-friendly, and excellent electron transport properties. However, its thermoelectric performance at room temperature is still low which extremely restricts its application. In this work, we report a high-power factor of 6.2 μWcm −1 K −2 and a record-high thermoelectric figure of merit, ZT of 0.35 at room temperature from the non-stoichiometric ZnSb-based thin film, fabricated by a facile magnetron cosputtering technique. Extensive characterizations reveal that all the prepared films have a primary ZnSb phase with good crystallinity, leading to high electrical conductivity. Meanwhile, the carrier concentration is optimized with Zn addition, which contributes to a high Seebeck coefficient, resulting in a decent power factor. Simultaneously, the Zn-rich films also show nanopores, Zn-rich nanophases, and Zn4 Sb3 nano inclusions. These induced nanostructures enhance the scattering of medium- and long-wavelength phonons, contributing to the reduction of lattice thermal conductivity. This work demonstrates that rational nanostructure manipulations can achieve high performance in ZnSb thin films, which possess potential applications for the fabrication of miniature thermoelectric devices. Graphical abstract: Image 1 Highlights: ZnSb-based thin films were fabricated by using a facile magnetron cosputtering technique. A decent power factor of 6.2 μWcm −1 K −2 of ZnSb-based thin films was achieved via carrier engineering. Multiple nanostructures lead to ultra-low lattice thermal conductivity. A record-high thermoelectric figure of merit of 0.35 at room temperature was achieved for non-stoichiometric ZnSb-based thin films.